Information Security Practice and Experience 8th International Conference, ISPEC 2012, Hangzhou, China, April 9-12, 2012. Proceedings - Ryan, Mark D.; Smyth, Ben.; Wang, Guilin; SpringerLink (Online service) (Berlin, Heidelberg : Springer Berlin Heidelberg, 2012)
This book constitutes the refereed proceedings of the 8th International Conference on Information Security Practice and Experience, ISPEC 2012, held in Hangzhou, China, in April 2012. The 20 revised full papers presented together with 7 work-in-progress papers were carefully reviewed and selected from 109 submissions. The papers are oranized in topical sections on digital signatures, public key cryptography, cryptanalysis, differential attacks, oblivious transfer, internet security, key management, applied cryptography, pins, fundamentals, fault attacks, and key recovery.
Keywords: Computer science; Computer Communication Networks; Data protection; Data encryption (Computer science).; Information storage and retrieval systems; Information Systems; Computer Science; Data Encryption; Systems and Data Security; Computer Communication Networks; Information Storage and Retrieval; Computers and Society; Management of Computing and Information Systems